1999
DOI: 10.1063/1.1149402
|View full text |Cite
|
Sign up to set email alerts
|

Some problems of the material choice for the first mirrors of plasma diagnostics in a fusion reactor

Abstract: We present the results of simulation experiments on the effect of the fusion reactor environment on the optical properties of the first mirrors for spectroscopy and laser diagnostics. We found the greatest effect on the degradation of mirror optical properties was due to charge exchange atoms. These atoms can affect mirror quality in two ways: by sputtering and by redeposition of material sputtered from other inner components of the vacuum chamber. The degradation rates of mirrors made of different metals and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
34
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 10 publications
4
34
0
1
Order By: Relevance
“…Here, the requirement for mirrors with line-ofsight views of the plasma is that the characteristic scale length of surface roughness developing due to sputtering by charge exchange atoms should be significantly less than the wavelength of the light being analyzed. It had been proposed [4] that the use of thin film mirrors or nanocrystalline mirrors with grain sizes much smaller than the required wavelength may be suitable for such applications. For example, for visible or near-infrared ranges of the spectrum mirrors with crystallite sizes ≤ 70 nm looked like could be acceptable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, the requirement for mirrors with line-ofsight views of the plasma is that the characteristic scale length of surface roughness developing due to sputtering by charge exchange atoms should be significantly less than the wavelength of the light being analyzed. It had been proposed [4] that the use of thin film mirrors or nanocrystalline mirrors with grain sizes much smaller than the required wavelength may be suitable for such applications. For example, for visible or near-infrared ranges of the spectrum mirrors with crystallite sizes ≤ 70 nm looked like could be acceptable.…”
Section: Discussionmentioning
confidence: 99%
“…The relief can be characterized with modern microscopy methods as optical interference microscopy, confocal laser scanning microscopy (CLSM), atomic force microscopy (AFM), scanning tunneling microscopy (STM), and scanning electron microscopy (SEM) with electron backscatter diffraction (EBSD). The longitudinal size of the developed roughness, i.e., the scale length of the step features, is determined by the grain size, and it would be expected that the scale length for the roughness would be similar to the grain size, as suggested in [4]. However, in experiments with Rh film mirrors [5] it was found that the sputtering of very fine-grain mirrors led to surface roughness with a longitudinal scale noticeably exceeding the grain size.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, such films have a fine-crystalline structure (≤100 nm). Therefore, it was expected [22] that the scale of microrelief, which appears after long-term sputtering may be appreciably shorter than the light wavelength range for which the mirror is applied.…”
Section: Film Mirrorsmentioning
confidence: 99%
“…Previously such effect was examined for copper and stainless steel mirrors [1,2] irradiated with high energy (1-3 MeV) Cu + and Cr + ions for simulating neutron irradiation. It was found that degradation of these mirrors under long term sputtering with hydrogen plasma occurs with approximately similar rate as that for the mirrors not preliminary bombarded with high energy metal ions.…”
Section: Introductionmentioning
confidence: 99%